2022
DOI: 10.3390/ijerph191711145
|View full text |Cite
|
Sign up to set email alerts
|

Person-Centered Practice in Hospitalized Older Adults with Chronic Illness: Clinical Study Protocol

Abstract: The aging trend in the population, the high rate of hospitalization, the affliction by multiple chronic illnesses, and the increased vulnerability of older people when hospitalized undoubtedly require a person-centered approach to healthcare—an approach that values a person’s participation in the healthcare relationship, supports shared decision making and mutual understanding, and respects a person’s values, preferences, and beliefs. However, despite widespread recognition that the adoption of such a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The high scores obtained on the different constructs raised the question of whether the participants' responses reflected their idealized practice or their real and current perception of daily care. Therefore, qualitative studies with multidisciplinary samples should be conducted to triangulate the results obtained in this study, as suggested by Vareta et al [21].…”
Section: Limitationsmentioning
confidence: 81%
See 1 more Smart Citation
“…The high scores obtained on the different constructs raised the question of whether the participants' responses reflected their idealized practice or their real and current perception of daily care. Therefore, qualitative studies with multidisciplinary samples should be conducted to triangulate the results obtained in this study, as suggested by Vareta et al [21].…”
Section: Limitationsmentioning
confidence: 81%
“…This study is part of a clinical study protocol [21] designed to provide recommendations for the development of person-centered practice in the daily care of hospitalized older adults with chronic diseases within an internal medicine department. The current practice analysis refers to how person-centered practice is perceived and identified in the context under study, considering that all principles and domains presented in the PCPF are fundamental for the implementation of this practice.…”
Section: Introductionmentioning
confidence: 99%
“…These elements of care were crucial for holistic care in patients with multimorbidity by coordinating referrals to specialists and allied healthcare workers. As multimorbidity management calls for a realignment of healthcare through a framework of patient-centred medicine 40,41 , primary care physicians or family physicians form the crux of such restructuring. Patients can be down-referred from tertiary and secondary to primary care wherever possible 42,43 .…”
Section: Discussionmentioning
confidence: 99%